Analysis of Public Perception and the Citizen’s Political Behavior to Determine the Electability of Candidates of Bogor Regency West Java Province Indonesia Year 2013-2018 - Zenju, Nandang Saefudin; Iskandar, Abubakar (American Scientific Research Journal for Engineering, Technology, and Sciences, 2016)
The research result indicate that 72.0 percent of the Regent Candidate year 2014 is Rachmat Yasin from PPP, as much as 3.2 percent is Karyawan Faturrachman from PDIP. While 2.0 percent is Iwan Setiawan from Gerindra. The purpose of this research is to analyze the structural determinism variable to determine the indicator of the election of the regent candidates, to analayze the behaviorism variable to determine the indicator of the election of the regent candidates, to analyze the utility variable to determine the indicator of the election of the regent candidates, and to analyze the psychology variable to determine the indicator of the election of the regent candidates. The design of the research is a survey. The research is conducted during a period of three month from October to December 2013. The research is conducted in Babakan Village Dramaga district. The sampling technique in this research is a gradually group of two or more group and the amount of sample is 100 sample. The data analysis in this research is Qualitative Analysis.The research result indicate that 27 respondence is signed up as a member of a political party, while 73 respondence is not signed up as a member of a political party. The research result indicate that 52.0 percent of the respondence expect free education for Senior High School students, while 31.0 percent of the respondence expect affordable and free health service. While 2.0 percent of the respondence expect that the Regency is free from traffic jam, comfortable and safe. The research result indicate that 50.0 percent request that the development priority scale order that they desire is the development and improvement of infrastructure, about 31,0 percent says the development of Public Hospital or RSUD, and 8,0 says the arangement of Public Transportation.